ZEE INDONESIA DI LAUT NATUNA UTARA: TELAAH KRITIS ATAS KLAIM NINE-DASH LINE TIONGKOK - Aslan Noor; Ajeng Pramesti; Samuel Alonso Girsang; Rizky Adi Nugraha; Alisha Jasmine; Raihana Fathiya (CV. Denasya Smart Publisher, 2026)
The North Natuna Sea is part of Indonesia's EEZ which has a wealth of biological and non-biological natural resources. Indonesia's sovereign rights in this region are expressly regulated under UNCLOS 1982. Their implementation is carried out through Law Number 5 of 1983 on the Indonesian EEZ, while Indonesia's ratification of UNCLOS itself was enacted through Law Number 17 of 1985. However, China's claims based on the Nine-Dash Line based on historical rights arguments have caused tensions and violations of Indonesia's sovereign rights in the region. This paper aims to critically examine the legal basis of Indonesia's sovereign rights in the North Natuna Sea EEZ, analyze the juridical weaknesses of China's Nine-Dash Line claims, and evaluate the various responses that Indonesia has taken in upholding its rights. The method used is normative legal research with a case and legislative approach. The results of the analysis show that normatively, Indonesia's legal position is very strong because UNCLOS does not recognize historical rights that go beyond the provisions of the convention, and the Permanent Court of Arbitration in 2016 has unequivocally stated that the Nine-Dash Line has no legal basis. However, there is a gap between normative strength and law enforcement capacity on the ground, as well as ambiguity in Indonesia's position in multilateral forums. Indonesia's response has shown positive developments through diplomatic, operational, and long-term policy measures, but it still requires increased regional consistency, capacity, and support. In conclusion, Indonesia's sovereign rights in the North Natuna Sea are legal under international law, but their effectiveness is highly dependent on the ability of state actors to enforce them in a sustainable manner